Enhanced coverage of all-inorganic perovskite CsPbBr3 through sequential deposition for green light-emitting diodes - Ng, Yan Fong (2020)
Film morphology has a major influence on the performance of halide perovskite semiconductors, where poor coverage and pinholes are generally detrimental and result in undesirable current leakage. All‐inorganic cesium lead bromide (CsPbBr3) has an advantage of improved stability especially under device operation, but the low solubility of the ionic precursor CsBr limits the coverage of the solution‐processed film. To tackle this, a sequential deposition technique is proposed whereby PbBr2 is first deposited on a planar substrate prior to exposure to a CsBr solution to initiate conversion to the desired CsPbBr3 phase. This approach essentially nullifies the solubility problem of CsBr and the final perovskite film coverage now chiefly depends on the initial PbBr2 concentration and the duration of exposure to the CsBr solution. With over 90 % film coverage achieved, a proof of concept perovskite light‐emitting diode (PeLED) with green emission at 527 nm has also been achieved, thereby demonstrating the feasibility of this methodology for future device fabrication.